Variations in Impacts of Climate Change on Giant Lobelia Species in East Africa - Radwa Salah; Mohamed Ezzat; Elijah Mbandi Mkala; Mohammed A. Dakhil; Tao Wan; Jun-Nan Wan (Diversity)
Climate change presents major challenges to global biodiversity and ecosystems. Related species distributed in the same region may exhibit differential response patterns to global climate change, resulting in divergent conservation strategies. East Africa is a critical hub for the diversity and distribution of giant Lobelia. In this study, we examined the potential distribution of seven giant Lobelia species (Lobelia aberdarica, L. telekii, L. gibberoa, L. bambuseti, L. deckenii, L. gregoriana, and L. rhynchopetalum) across six East African countries (Kenya, Ethiopia, Tanzania, Rwanda, Uganda, and Burundi) under projected climate change scenarios both RCP4.5 and RCP8.5. Species distribution models yielded high predictive accuracy (TSS > 0.8), with the mean temperature of the driest quarter (bio9) emerging as the most influential climatic variable determining future species distribution. The study found considerable variation in the species’ climatic niches, identifying distinct regions of climatically suitable habitats for each. Lobelia species at lower altitudes, such as L. giberroa and L. bambuseti, showed greater stability and expansion. In comparison, species at higher altitudes, such as L. telekii, L. deckenii, and L. rhynchopetalum, faced significant contraction in suitable habitats. These high-altitude species are particularly vulnerable and require urgent conservation interventions. This research highlights the importance of climate change considerations in the conservation of Lobelia species and provides a basis for developing targeted sustainable conservation.